Sistem Pendukung Keputusan Pemilihan Siswa Peserta Olimpiade Pada Jenjang Sekolah Dasar Di Kecamatan Gunung Maligas Dengan Menggunakan AHP - Erozeki Sialagan; Rahmat Widia Sembiring; S Suhada (LPPM STIKOM Tunas Bangsa, 2019)
This study aims to assist relevant parties in making selections in the selection of olympic students at the Elementary School Level in Gunung Maligas District. The method used is the AHP method. Source of research data obtained by observing and interviewing the school. The research data samples were four elementary schools in Gunung Maligas sub-district, among others: 1) SDN 096780 Kampung tape, 2) SDN 097806 Kabupaten Simalungun, 3) SDN 091263 Karang Sari and 4) SDN 098145 Karang Sari. The assessment criteria used as a basis for assessments include: Olympic Experience, Intelligence, Academic Ability (Science Report Score or Mathematics) and Olympic Capabilities. The results of the study showed that alternative 4 with a value of 0.356 (first rank) was recommended by Olympic student participants.